Ambiguity attitudes in the loss domain: decisions for self versus others - Xu, Yilong; Xu, Xiaogeng; Tucker, Steven (Economics letters, 2018)
We study whether people’s ambiguity attitudes differ when deciding for themselves or for others in the loss domain. We find no systematic differences in ambiguity attitudes between self- and other-regarding decision-making. Our results are consistent with the loss part of the fourfold pattern of ambiguity attitudes.